Lithium intercalation into double rare earth chromates - Melnikov, Petr [UNESP] (Elsevier B.V., 1994)
Lithium intercalation into double rare earth chromates was carried out. It was found that the compounds NaxLi1-xLa(CrO4)2 belong to the NaLa(CrO4)2 structural type and may be recommended as fast ionic conductors. At small values of x a third polymorphous modification of LiLa(CrO4)2 can be stabilized. Attempts to intercalate lithium into CsLa(CrO4)2 lead to collapse of the lamellar network with the formation of LaCrO4 and alkaline chromates. Ion exchange Li+/H+ data are consistent with these considerations. © 1994.
Keywords: Crystal atomic structure; Ion exchange; Ionic conduction in solids; Lithium; Rare earth compounds; Sodium compounds; Double rare earth chromates; Lithium intercalation; Polymorphous modification; Chromates